2018
DOI: 10.1177/0308575918790433
|View full text |Cite
|
Sign up to set email alerts
|

Retaining foster carers during challenging times: the benefits of embedding reflective practice into the foster care role

Abstract: Retaining high quality foster carers and helping them to manage the intense emotional impact of caring for young traumatised children is still a major challenge. While foster carer training helps in the short term, international findings suggest that training and support structures alone may not sustain foster carers when times get tough. This article considers the benefits of embedding reflective practice into the role of foster carers. It draws on a qualitative study of five foster carers and two birth mothe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…The young person's rejection and mistrust may impair the parent's mentalizing capability, leading to vicious circles in which the parent, in turn, misrepresents the child's mental states leading to further relational problems (Ensink et al, 2016;Onions, 2018;Redfern et al, 2018). In addition, if the foster parent's capacity to reflect on the young person's mental states is impaired, the parent may not notice changes in mental health of the young person, being preoccupied by regulating their own troubled affects.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The young person's rejection and mistrust may impair the parent's mentalizing capability, leading to vicious circles in which the parent, in turn, misrepresents the child's mental states leading to further relational problems (Ensink et al, 2016;Onions, 2018;Redfern et al, 2018). In addition, if the foster parent's capacity to reflect on the young person's mental states is impaired, the parent may not notice changes in mental health of the young person, being preoccupied by regulating their own troubled affects.…”
Section: Discussionmentioning
confidence: 99%
“…Parental caregiving is linked to mentalizing; i. e. the parents' ability to reflect on their own mental states and their child's mental states (Ensink, Normandia, Plamondon, Berthelot, & Fonagy, 2016;Feeney & Woodhouse, 2016). Mentalizing, operationalized as reflective functioning, is one important component of the caregiving system (Ensink et al, 2016;Feeney & Woodhouse, 2016;Onions, 2018). Improvements in reflective functioning has been linked to improvements in caregiving quality (Suchman, DeCoste, Leigh, & Borelli, 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result, carers often experience higher anxiety, depression and stress than the general population (Farmer, 2005). Research has shown that to retain high-quality carers, support structures need to be implemented to assist carers with the emotional impact of caring for a child with challenging behaviours (Onions, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…In terms of child psychotherapists' consultancy work with foster carers, Ironside (2004Ironside ( , 2009Ironside ( , 2012 adapted the psychoanalytic infant observation method for use with foster carer groups, finding that it helped carers to recognise and separate their own feelings from instances when children were projecting emotions into them, and how to respond to their behaviour. More recently, Onions (2018) has written about the embedding of a reflective practice culture with foster carers at the residential Mulberry Bush School, finding that after 12 months' support the carers reported feeling less overwhelmed and that their child was easier to parent.…”
Section: Introductionmentioning
confidence: 99%